2019
DOI: 10.5249/jivr.v11i2.1102
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and its predictors among elementary students

Abstract: : Background: Aggression is the most significant psychopathological risk factor. It is a multifaceted construct and can affect students’ social, mental and physical health. The present study was conducted to investigate factors associated with aggression among elementary school girls and boys using the theoretical framework of Social Cognitive Theory in Kermanshah city, Iran. Methods: The cross-sectional study was conducted on 900 students, including 445 gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
2
7
0
8
Order By: Relevance
“…Embora a busca pelos artigos tenha considerado o período de 2015 a 2020, foram identificadas produções apenas nos anos 2017, 2018 e 2019. As pesquisas foram realizadas em dez países (Alemanha, Austrália, Bangladesh, Bélgica, China, Holanda, Inglaterra, Irã, Nova Zelândia e Taiwan), sendo a maior parte localizada na Europa (Bonell et al, 2018;Desmet et al, 2018;Niejenhuis et al, 2019;Zagorscak et al, 2018), seguido por Ásia (Lang, 2018;Nieh & Wu, 2018;Salimi et al, 2019;Sultana et al, 2018) e Oceania (Cross et al, 2018;Farmer et al, 2017). Nenhum estudo foi realizado na América ou na África, conforme apresentado na Tabela 1.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Embora a busca pelos artigos tenha considerado o período de 2015 a 2020, foram identificadas produções apenas nos anos 2017, 2018 e 2019. As pesquisas foram realizadas em dez países (Alemanha, Austrália, Bangladesh, Bélgica, China, Holanda, Inglaterra, Irã, Nova Zelândia e Taiwan), sendo a maior parte localizada na Europa (Bonell et al, 2018;Desmet et al, 2018;Niejenhuis et al, 2019;Zagorscak et al, 2018), seguido por Ásia (Lang, 2018;Nieh & Wu, 2018;Salimi et al, 2019;Sultana et al, 2018) e Oceania (Cross et al, 2018;Farmer et al, 2017). Nenhum estudo foi realizado na América ou na África, conforme apresentado na Tabela 1.…”
Section: Resultsunclassified
“…Quase todos os estudos foram realizados com participantes do sexo masculino e sexo feminino, com exceção de um estudo (Salimi et al, 2019) que interviu exclusivamente com o sexo masculino e outro que não especificou o sexo dos participantes (Niejenhuis et al, 2019). Destaca-se que apenas três artigos desta revisão se propuseram a relatar separadamente os efeitos das intervenções para meninos e meninas.…”
Section: Autoria (Ano)unclassified
See 2 more Smart Citations
“…The literature shows that students with aggressiveness traits in the school environment are at risk of having academic failure, social maladjustment, and lifelong negative and wrong behaviors [27][28][29]. Additionally, it is reported that aggressive behaviors are related to various negative outcomes in adulthood, including low unemployment, social isolation, various social problems, and impaired physical health [19,30].…”
Section: Introductionmentioning
confidence: 99%